The 4BE quinqunx: A model for obesity pathogenesis - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
For obesity management to be effective, one must appreciate its causes and consequences. To do so, the seemingly complex science of obesity must be made simpler. A model which helps us explain its causes, contributory factors, as well as potential corrective measures, is needed. We share the 4BE winged quincunx model of obesity etiopathogenesis. Four central players - the Brain, Bowel, Beta/alpha cell and Bulk (adipose tissue)- form a causative quadruple, with four wings- Environmental determinants, Endocrine factors, Enteric microbiome and Extraneous limitations. The centre of the quincunx is occupied, in a stylish manner, by the ABC of weight management: Attitude, Behaviour and Choices. The 4BE concept makes it easy for health care professionals to understand, and explain, obesity. KEYWORDS: Biochemistry, endocrinology, obesity, overweight, pathogenesis, person centred care, therapeutic patient education